Pola Pengasuhan Orangtua Pada Anak Usia Dini di Suku Dayak - Siti Syaropah; RR Deni Widjayatri (Insititut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to describe the parenting pattern of early childhood in the Dayak tribe. In this research, the method used is literature study, in this method data collection is done by collecting data based on the results of research that has been done previously that analyzes the research in order to answer the existing problems. Results Based on a literature study on parenting patterns of early childhood in the Dayak tribe, it shows that Dayak parents provide parenting to their children using permissive parenting but applying more democratic (authoritative) parenting. Permissive parenting is a parenting style that provides leeway and observation, is less demanding, not controlling. While the democratic or authorative style of parenting is a parenting style that gives freedom or surrenders everything according to the child's wishes but will always be supported by parents. And with parents who apply this parenting pattern, they tend to be open to parents and have a good and cheerful personality.